Plant Dynamic Metabolic Response to Bacteriophage Treatment After Xanthomonas campestris pv. campestris Infection - Papaianni, Marina; Paris, Debora; Woo, Sheridan L.; Fulgione, Andrea; Rigano, Maria Manuela; Parrilli, Ermenegilda; Tutino, Maria L.; Marra, Roberta; Manganiello, Gelsomina; Casillo, Angela; Limone, Antonio; Zoina, Astolfo; et al. (Frontiers in Microbiology, 2020)
Periodic epidemics of black rot disease occur worldwide causing substantial yield losses. Xanthomonas campestris pv. campestris (Xcc) represents one of the most common bacteria able to cause the above disease in cruciferous plants such as broccoli, cabbage, cauliflower, and Arabidopsis thaliana. In agriculture, several strategies are being developed to contain the Xanthomonas infection. The use of bacteriophages could represent a valid and efficient approach to overcome this widespread phenomenon. Several studies have highlighted the potential usefulness of implementing phage therapy to control plant diseases as well as Xcc infection. In the present study, we characterized the effect of a lytic phage on the plant Brassica oleracea var. gongylodes infected with Xcc and, for the first time, the correlated plant metabolic response. The results highlighted the potential benefits of bacteriophages: reduction of bacterium proliferation, alteration of the biofilm structure and/or modulation of the plant metabolism and defense response.